2019
DOI: 10.1038/s41598-019-55277-6
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity Processing Bias Induced by Depressed Mood Is Associated with Diminished Pleasantness

Abstract: Depressed individuals are biased to perceive, interpret, and judge ambiguous cues in a negative/pessimistic manner. Depressed mood can induce and exacerbate these biases, but the underlying mechanisms are not fully understood. We theorize that depressed mood can bias ambiguity processing by altering one’s subjective emotional feelings (e.g. pleasantness/unpleasantness) of the cues. This is because when there is limited objective information, individuals often rely on subjective feelings as a source of informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Attentional bias for negative events might be notable characteristics of both MDD and subclinical depression (Lin et al, 2019). Thus, our findings of altered HEP in HDR individuals may highlight their negative bias in predictive coding processing.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Attentional bias for negative events might be notable characteristics of both MDD and subclinical depression (Lin et al, 2019). Thus, our findings of altered HEP in HDR individuals may highlight their negative bias in predictive coding processing.…”
Section: Discussionmentioning
confidence: 63%
“…During the heartbeat counting task, HEPs reflected the precision-weighted prediction error for each heartbeat (Banellis and Cruse, 2020). Moreover, attentional bias for negative events might be notable characteristics of individuals with MDD (Gotlib and Joormann, 2010) and with subclinical depression (Lin et al, 2019). It has been shown that depressive trait may relate to reduced precision in prediction and increased precision in prediction error (Badcock et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implicit measure of cognitive bias implemented in this study has originally been developed in the context of animal models of depression [77][78][79] and translated for human research [80][81][82][83]. Previous studies in humans have consistently reported an association between a more negative interpretation bias and elevated levels of depressiveness as well as experimentally induced depressive mood in general population samples [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…The ambiguous cue-conditioning paradigm is an indirect measure of cognitive bias based on evaluative conditioning. The paradigm has been developed in animal studies [77][78][79] and translated for human research [80][81][82][83]. In the current study, we implemented a visual version of the task (Fig.…”
Section: Stimuli Task and Proceduresmentioning
confidence: 99%